Histopathologic Parameters at Diagnosis as Early Predictors of Histologic Remission along the Course of Ulcerative Colitis - Jesús K. Yamamoto-Furusho; Braulio Martínez-Benítez; Germán E. Sánchez-Morales (Gastroenterology Research and Practice)
Background. Currently, the treatment goal in ulcerative colitis (UC) is to achieve clinical and endoscopic remission; nevertheless, histologic remission is a potential new treatment goal since it is associated with favorable long-term clinical outcome lower rates of hospitalization, complications, and colectomies. Aim. Evaluate clinical and histopathologic characteristics at diagnosis as potential predictors of histologic remission in patients with ulcerative colitis. Methods. This is a retrospective cohort study from 2007 to 2014, including 260 patients. Clinical and demographic information and Mayo endoscopic and Riley histologic grade were obtained accordingly with the follow-up. Histological evaluation was made for all 260 patients; fifty-six patients with histologic remission at the follow-up underwent separate evaluation of mucosal biopsy at the moment of diagnosis. Univariate and multivariate analyses were applied to data from these 56 patients to identify histologic features at diagnosis associated with histologic remission during follow-up. The odds ratio (OR) was determined as a measure for the strength of association. A P value of less than 0.05 was taken as a level of significance. Results. The frequency of histologic remission according to the Riley index in our study group was 21.5%. Factors associated with histologic remission were treatment with steroids (P=0.01, OR=0.38, CI 95%=0.16‐0.90), reduced mucin production (P=0.02, OR=0.23, CI 95%=0.06–0.86), and less than 10 eosinophils per high power field (P=0.001, OR=6.66, CI 95%=2.03–21.84). Conclusion. Factors that impair histologic remission in patients with ulcerative colitis were treatment with steroids and reduced mucin production; meanwhile, less than 10 eosinophils per high power showed a predictive value for histologic remission.